Better record keeping and documentation techniques for chairs. - Kristi Haik; Beth Zimmer (Academic Chairpersons Conference Proceedings, 2020)
Presenters and participants will discuss tips and techniques for better record keeping and documentation practices in the department office. Areas of discussion will include suggestions for better record keeping strategies and how to properly document scheduled and impromptu meetings, meetings with faculty for promotion, tenure and review, and meetings with students and parents. We will provide take-home examples to make the day-to-day operations of the office run more smoothly.
Keywords: record keeping; documentation; email; notes; protect